Preparation of an Aroma Fraction from Dried Bonito by Steam Distillation and Its Effect on Modification of Salty and Umami Taste Qualities. Issue 2 (31st December 2015) - Ogasawara, Yasushi; Mochimaru, Shinsuke; Ueda, Reiko; Ban, Masayasu; Kabuto, Shizuya; Abe, Keiko
Abstract: To study the effects of dried bonito aroma on taste perception, dried bonito aroma fraction (DBAF) as a steam distillate in liquid was added to the salt solutions containing 5 different salt concentrations (0.68% to 1.5% [w/v]) before sensory evaluations. Perception of the taste qualities of salt solutions with added DBAF varied depending on the salt concentration. At low salt concentrations (0.68% to 0.83%), after‐taste intensity of saltiness and overall taste intensity were significantly enhanced by the addition of DBAF. This suggests that DBAF can be applied to a low‐salt seasoning at these salt concentrations. Umami taste intensity was significantly enhanced by the addition of DBAF at all salt concentrations (0.68% to 1.5%). The addition of heat‐treated DBAF, which no longer had the dried bonito odor, exerted no significant influences on any taste descriptors. As the result of gas chromatography–mass spectrometry analysis, sulfur‐containing compounds, pyrazines, alcohols, and phenols were contained in DBAF and not detected in heat‐treated DBAF. Because these compounds contributed to the dried bonito odor, the taste modifications were thought to be induced by these compounds. The effects of the DBAF on Japanese noodle soup ( mentsuyu ) were also examined. The saltiness intensity of 1.2% salt concentration of mentsuyu containing both DBAF and DBS (dried bonito stock) as a hot water extract of dried bonito was not significantly differ from that of 1.5% salt concentration of mentsuyu not containing any of them. It will thus be possible to develop a reduced salt seasoning by combining DBAF and DBS.